(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
The 18th century witnessed the emergence and rise of the English novel as a dominant literary form, driven by socio-political changes, increased literacy, and advancements in printing technology. This article explores the early development of the English novel, highlighting the contributions of pioneering authors such as Daniel Defoe, Samuel Richardson, and Henry Fielding. Through an examination of narrative techniques—such as Defoe’s realism, Richardson’s epistolary form, and Fielding’s use of satire—this study underscores the novel’s evolution from its precursors. Additionally, the article delves into the social commentary embedded within these early works, addressing themes of class, gender, morality, and the individual’s relationship with society. By analyzing the intersection of narrative innovation and social critique, this article illuminates the novel’s role in reflecting and shaping 18th-century English culture